If you can solve this puzzle, I'll send you a picture of myself naked sprawled out on a bear skin rug.
Try to derive MU from MI following these rules:
1) If you possess a string whose last letter is I, you can add on a U at the end, e.g. if you have MUMI, you may change it to MUMIU.
2) Suppose you have Mx. Then you may change it to Mxx, e.g.
MU --> MUU, MIUI --> MIUIIUI, MUMI --> MUMIUMI.
3) If a string contains III, you may replace it with U,
e.g. MIII --> MU, IIIIIII --> UUI, UIU, IUU or just IIIIU.
4) If UU occurs in a string, you may drop it,
e.g. MUUU --> MU, MIUUIM --> MIIM.
Points of clarification:
i) The order is important - MU is not equivalent to UM.
ii) The rules are not reversible,
e.g. you cannot say MU --> MIII by applying Rule 3 backwards.
Try to derive MU from MI following these rules:
1) If you possess a string whose last letter is I, you can add on a U at the end, e.g. if you have MUMI, you may change it to MUMIU.
2) Suppose you have Mx. Then you may change it to Mxx, e.g.
MU --> MUU, MIUI --> MIUIIUI, MUMI --> MUMIUMI.
3) If a string contains III, you may replace it with U,
e.g. MIII --> MU, IIIIIII --> UUI, UIU, IUU or just IIIIU.
4) If UU occurs in a string, you may drop it,
e.g. MUUU --> MU, MIUUIM --> MIIM.
Points of clarification:
i) The order is important - MU is not equivalent to UM.
ii) The rules are not reversible,
e.g. you cannot say MU --> MIII by applying Rule 3 backwards.
VIEW 9 of 9 COMMENTS
No wait... how 'bout double or nothing? Analytically integrate under a gausian for an arbitrary boundary... just joking.
One other thing, I don't think this picture will contain a bear skin rug... I'm not too cool with killing animals.